TiO2-PDMS Super Hydrophilic Coating with Self-Cleaning and Antimicrobial Properties - Dessy Ariyanti; Afiatin Afiatin; Pury Diana Shintawati; Aprilina Purbasari (Jurnal Kimia Sains dan Aplikasi, 2021)
In this paper, self-synthesized TiO2 nanoparticle was used as a coating material with the addition of polydimethylsiloxane (PDMS) on the surface of the glass and ceramic substrate via spray coating. The self-cleaning properties of the coating with photocatalytic activity mechanism were observed under irradiation of black lamp as well as surface wettability. The antimicrobial properties and the morphology under a scanning electron microscope were also investigated. The results showed that the coating exhibited self-cleaning properties, as demonstrated by the photocatalytic degradation of methylene blue up to 80% and wettability as a super hydrophilic layer with a water contact angle less than 10° for both glass and ceramic substrate. The coating also shows an antimicrobial property by extending the radius of microbial growth up to 67% compared to the uncoated sample. 3% TiO2 addition with 50% w/w PDMS is the optimum coating ratio for maximum photocatalytic activity, super hydrophilic, and antimicrobial properties.